KUALITAS KEBERANIAN MARTHA TILAAR (PEMIMPIN MARTHA TILAAR) DALAM KONTEKS BISNIS BERBASIS TANAMAN UNTUK KECANTIKAN DAN OBAT - Nuah P. Tarigan; Christian Siregar; Hondi Panjaitan (Media Riset Bisnis & Manajemen, 2012)
By conducting research on the quality of the courage of the writers and all who read this research will increasingly aware that quality of courage these elements can be built, so it is not just a personality, but also the behavior of an individual student or professional workers and entrepreneurs even public officials in the territory of the Republic of Indonesia this is characteristic of togetherness or "solid " . Related journals and a bold attitude to the role of women, defect or disability is currently difficult to find, so I see that building a bold stance was not only important but extremely important , amid the extent of the "battle " between nations to establish itself, the community and nation, not only physically, builds its course , but also to the soul as a whole . Its meaning will also be increasingly important if the aim is right on target and heading into a future full of optimism and spirit of cooperation in all fields. Martha Tilaar is one example of courageous leaders , who dare oppose not only because she was a woman , but also the middle of the day in which very little number of entrepreneurs and entrepreneurial women like him.Keywords: Qualities of courage, Personality, Behavior, Handicapped or disability, Entrepreneur